Japan's maritime security strategy the Japan Coast Guard and maritime outlaws - Black, Lindsay (Critical Studies of the Asia-Pacific, 2014)
In recent times, international society has countered a myriad of 'outlaw' threats at sea, including piracy, terrorism, the proliferation of Weapons of Mass Destruction (WMD) and the threat posed by 'rogue states'. Whilst the US has promoted 'coalitions of the willing' and sought to transform international maritime law in response to these 'outlaws', Japanese governments have developed an innovative maritime security strategy centering on the Japan Coast Guard (JCG). Concerned by Japan's international image as a former imperialist power, Tokyo has relied upon the identity of the JCG as a law enforcement and rescue organization to garner support for its maritime security strategy. Japan's non-military efforts have developed the capacities of states and built institutions in the Southeast Asian region and beyond. The JCG's response to maritime 'outlaws' belies characterizations of Japan as a passive state that does not contribute to international order.